2012
DOI: 10.5888/pcd9.110208
|View full text |Cite
|
Sign up to set email alerts
|

Policy Implications for Local Application of the 2009 Youth Risk Behavior Survey, Duval County, Florida

Abstract: Introduction Youth Risk Behavior Survey (YRBS) data have rarely been analyzed at the subcounty level. The purpose of this study was to explore the feasibility of such analysis and its potential to inform local policy and resource allocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…In this study, one of the most notable high-rate clusters occurring in a metropolitan area included part of Jacksonville, located in Duval County in northeastern Florida. An analysis of 2007 data also reported sub-county level disparities in diabetes prevalence, emergency department visits, hospitalizations, and deaths in Duval County [ 22 ]. Compared to the rest of the county, residents of central Jacksonville had higher burdens of all the outcomes investigated in that study [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, one of the most notable high-rate clusters occurring in a metropolitan area included part of Jacksonville, located in Duval County in northeastern Florida. An analysis of 2007 data also reported sub-county level disparities in diabetes prevalence, emergency department visits, hospitalizations, and deaths in Duval County [ 22 ]. Compared to the rest of the county, residents of central Jacksonville had higher burdens of all the outcomes investigated in that study [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The disadvantaged neighborhood clinics were located in what had been identified by the local Health Department as Health Zone 1, a 6 zip-code part of the city/county that is 80% minority residents with high poverty rates and prevalent health disparities. 38 , 39 …”
Section: Methodsmentioning
confidence: 99%
“…The disadvantaged neighborhood clinics were located in what had been identified by the local Health Department as Health Zone 1, a 6 zip-code part of the city/county that is 80% minority residents with high poverty rates and prevalent health disparities. 38,39 Patient selection within the clinics started in the morning of clinic operations as early as data collection could be arranged, following: IRB approval, training of the patient navigators (PNs), and coordination with clinic administrators. Following the beginning of data collection, patients were systematically seen in the clinic settings as they presented for medical appointments.…”
Section: Sample Populationsmentioning
confidence: 99%
“…The 5 zip code urban core of the city/county is 80% African American, and innovative surveillance techniques have documented major burdens of obesity in the community. For example, the diabetes-related mortality of Duval County is 50% higher than state average and higher than any of the 10 other larger counties in Florida, and diabetes mortality and diabetes-related hospitalization and emergency room use are much more prevalent in the African American community (three to four times the rates) than other parts of the county (Livingood et al, 2010). Innovative applications of the Youth Risk Behavioral Surveillance surveys in Duval County have shown that the prevalence of sedentary behaviors and low levels of physical activity are particularly high in the areas of the city that are predominantly African American (Livingood et al, 2012).…”
mentioning
confidence: 94%
“…For example, the diabetes-related mortality of Duval County is 50% higher than state average and higher than any of the 10 other larger counties in Florida, and diabetes mortality and diabetes-related hospitalization and emergency room use are much more prevalent in the African American community (three to four times the rates) than other parts of the county (Livingood et al, 2010). Innovative applications of the Youth Risk Behavioral Surveillance surveys in Duval County have shown that the prevalence of sedentary behaviors and low levels of physical activity are particularly high in the areas of the city that are predominantly African American (Livingood et al, 2012). The prevalence of these early risk factors for obesity within the predominantly African American parts of the city are particularly ominous, given the high rates of obesity-related disease in the community.…”
mentioning
confidence: 99%